(untitled) (Pedagogy of Higher and Secondary Education, 2010)
The article shows the problem of the future teachers’ formation of readiness to professional activity ( the prevention of deviation behavior of the teenagers), the different approaches of definition of concept "readiness" for professional activity in die scientific literature are treated and the own definlion of concept "readiness" is sent.